Imaging for Forensics and Security From Theory to Practice - Bouridane, Ahmed; SpringerLink (Online service) (Boston, MA : Springer US, 2009)
Imaging for Forensics and Security: From Theory to Practice provides a detailed analysis of new imaging and pattern recognition techniques for the understanding and deployment of biometrics and forensic techniques. These techniques can be used for practical solutions to increase security. The material contains a collection of the recent advances in the technology ranging from theory, design, and implementation to performance evaluation of biometric and forensic systems. It also addresses new methods such as the multiscale approach, directional filter bank, and wavelet maxima for the development of practical solutions to biometric problems. The author introduces a new forensic system based on shoeprint imagery with advanced techniques for use in forensics applications. The material also presents the concept of protecting the originality of biometric images stored in databases against intentional and unintentional attacks and fraud detection data in order to further increase the security. Imaging for Forensics and Security: From Theory to Practice is a useful tool for researchers and practitioners in imaging for security and forensics.
and Preliminaries on Biometrics and Forensics Systems -- Data Representation and Analysis -- Improving Face Recognition Using Directional Faces -- Recent Advances in Iris Recognition: A Multiscale Approach -- Spread Transform Watermarking Using Complex Wavelets -- Protection of Fingerprint Data Using Watermarking -- Shoemark Recognition for Forensic Science: An Emerging Technology -- Techniques for Automatic Shoeprint Classification -- Automatic Shoeprint Image Retrieval Using Local Features.
Keywords: Computer science; Forensic medicine; Computer graphics; Pattern recognition; Electrical engineering; Computer Science; Pattern Recognition; Signal, Image and Speech Processing; Forensic Medicine; Computer Imaging, Vision, Pattern Recognition and Graphics; Electrical Engineering; Electronic books